Contribution of Management Consultancy towards Organizations#x2019; Financial Performance: A Case of Willy Enterprises Ltd in Arusha Tanzania (Global Journal of Management and Business Research, 2018)
Abstract- Scholars and business practitioners agree that Management Consultancy usage in a firm is an essential tool for rapid organizational growth in all dimensions. Management consulting assists business organizations in increasing business productivity by analyzing existing business troubles and flaws in business plans that hinder the growth of a company (Kopoka 2011). Managers from various departments at Willy Enterprises Ltd had different opinions about what happened before and after usage of management consultants; evidence show that the company had poor performance before usage of consulting services. In this paper two objectives guide the study: to what extent does the organization use Management Consultancy services and to compare the organization#x2019;s financial performance before and after engaging Management Consultants. Used data were gathered in 2012 through the cross-sectional survey by way of questionnaires, interviews and documentary analysis. The sample of the participants was forty-five (45) respondents from the different managerial position of the company and its client-firms and company#x2019;s financial statements for twelve (12) years from 1999-2010. In analyzing performance financially, this study decided to use ratio analysis as it is believed to be a robust measure of financial performance as compared to all others (Wood and Sangster, 2011). The findings here are part of Master Dissertation on Contribution of Management Consultancy towards Organizational Performance: A Case of Willy Enterprises Ltd in Arusha Tanzania.
Keywords: management; consultancy; organization; financial performance